1995
DOI: 10.1093/carcin/16.11.2637
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of 3-methyladenine and 3-ethyladenine after controlled exposure to tobacco smoke

Abstract: The urinary excretion of the DNA alkylation products 3-methyladenine (3-MeAde) and 3-ethyladenine (3-EtAde) after controlled exposure to cigarette smoke over a period of 4 days was determined by competitive radioimmunoassay after separation by HPLC. Twenty-four hour urine samples were collected from five smokers and five non-smokers. Days 1 and 3 (control days) were without smoking, on days 2 and 4 smokers consumed 24 cigarettes each within 8 h in an unventilated room (45 m3) in the presence of non-smokers. Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 0 publications
4
24
0
Order By: Relevance
“…The no smoking group also had a significantly lower level (p B/0.0001) of 3-MeAd than the CC2 group at day 8. The 3-MeAd excretion levels in CC1 and CC2 smokers were comparable with the data for smokers reported by Kopplin et al (1995), but those in the no smoking group was lower than in non-smokers ('passive smokers') reported by the same authors. For Evaluation of urinary biomarkers of exposure to cigarette smoke 45 Biomarkers Downloaded from informahealthcare.com by Mcgill University on 12/03/14 3-EtAd, the results are difficult to interpret because, first, the levels in the CC1 and no smoking groups did not show any significant change relative to their respective baselines; second, there was no detectable difference between the CC1 and no smoking groups either at baseline or at day 8; third, there was no within subjectcorrelation between baseline and day 8 for the CC1 group; and forth, the levels in the CC2, EHCSS1 and EHCSS2 groups decreased significantly relative to their respective baseline levels.…”
Section: -Mead and 3-etad As Biomarkerssupporting
confidence: 84%
See 1 more Smart Citation
“…The no smoking group also had a significantly lower level (p B/0.0001) of 3-MeAd than the CC2 group at day 8. The 3-MeAd excretion levels in CC1 and CC2 smokers were comparable with the data for smokers reported by Kopplin et al (1995), but those in the no smoking group was lower than in non-smokers ('passive smokers') reported by the same authors. For Evaluation of urinary biomarkers of exposure to cigarette smoke 45 Biomarkers Downloaded from informahealthcare.com by Mcgill University on 12/03/14 3-EtAd, the results are difficult to interpret because, first, the levels in the CC1 and no smoking groups did not show any significant change relative to their respective baselines; second, there was no detectable difference between the CC1 and no smoking groups either at baseline or at day 8; third, there was no within subjectcorrelation between baseline and day 8 for the CC1 group; and forth, the levels in the CC2, EHCSS1 and EHCSS2 groups decreased significantly relative to their respective baseline levels.…”
Section: -Mead and 3-etad As Biomarkerssupporting
confidence: 84%
“…Prevost et al (1993) reported rapid eliminations of deuterium labelled 3-MeAd and 3-EtAd in human following ingestion: within 24 h, /90% of 3-MeAd was excreted and 67 Á/74% of 3-EtAd was excreted. In the two reported controlled studies (Kopplin et al 1995, Prevost & Shuker 1996, immediate rising and falling of excretion levels of these alkyladenines in smokers on alternating smoking and no smoking days were observed, which is consistent with the normally rapid repair mechanisms following DNA alkylation. The high 3-EtAd excretion level in the no smoking group at day 8 could not be explained by dietary confounding either because the menus at baseline and at day 8 were identical.…”
Section: -Mead and 3-etad As Biomarkerssupporting
confidence: 70%
“…Point mutations induced by alkylating agents originate principally from O 6 -alkylguanine and O 4 -alkylthymine (10). Alkylated adenine derivatives have been found in the urine of smokers (11) and procarcinogenic DNA adducts that arise from exposure to methylating agents have been detected in human colorectal DNA at levels comparable with those that cause adverse effects in model systems (2).…”
mentioning
confidence: 99%
“…DNA can be alkylated by a variety of agents that occur both exogenously and endogenously (2,3). Alkylating agents are used in some chemotherapy treatments, and alkylated DNA bases have been detected in the urine of smokers (4). AlkB catalyzes demethylation of DNA and along with AlkA, AidB, and Ada is one of four proteins involved in the adaptive response to alkylation damaged DNA in Escherichia coli (5).…”
mentioning
confidence: 99%